1997
DOI: 10.1007/bf02920445
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-supported oil extraction fromJatropha curcas Seeds

Abstract: Jatropha curcas is a tropical plant widely distributed in arid areas. The seeds contain about 55% of oil, which is mainly used for the production of soap as a fuel and after transesterification as biodiesel. Various methods for recovering of oil from the seeds, including extraction with organic solvents and water, have been investigated. Compared to hexane extraction (98%) the oil extraction using water only yielded 38% of the total oil content of the seeds. Using several cell wall degrading enzymes during aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…This is in good agreement with the Jatropha oil yield of 85.6% and 74% extracted by using protease of Alcalase (Novo Nordisk, Denmark) and Protizyme (Jaysons Agritech, India), respectively (Shah et al 2005; Winkler et al 1997). The use of Viscozyme (Novo Nordisk, Denmark) as a hemicellulase/cellulase formula gave a comparable oil yield of 70% (Winkler et al 1997). …”
Section: Discussionsupporting
confidence: 81%
“…This is in good agreement with the Jatropha oil yield of 85.6% and 74% extracted by using protease of Alcalase (Novo Nordisk, Denmark) and Protizyme (Jaysons Agritech, India), respectively (Shah et al 2005; Winkler et al 1997). The use of Viscozyme (Novo Nordisk, Denmark) as a hemicellulase/cellulase formula gave a comparable oil yield of 70% (Winkler et al 1997). …”
Section: Discussionsupporting
confidence: 81%
“…Based on experimental work conducted by Campbell and Pitcher (3), who observed that the amount of liquid is in a strong relation with the speed of the pressure shockwave, it was decided that the amount of the liquid must be observed in detail. Methanol (17,18) or n-hexane (extraction efficiency 98% [30]) are most frequently used solvents; however, there are concerns about the environmental impacts (1). Safe ethanol is generally a weak solvent, but its application accelerated by microwaves (8), reverse osmosis or ultrafiltration (6, 13) is well known.…”
Section: Resultsmentioning
confidence: 99%
“…Other authors (7,12,15) discuss similar values. Winkler et al (30) reported a yield of 38 % when there are no chemicals used. However, yields of 86 % may be achieved with hydrolysing enzymes (alkaline protease).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike its competitors, aqueous enzymatic extraction is eco‐friendly, does not require extensive energy for solvent separation and has less fire/explosion risks. Several researchers have exploited various enzymes to extract jatropha oil . Enzymatic extraction has also been combined with ultrasound and three‐phase partitioning to enhance oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have exploited various enzymes to extract jatropha oil. [9][10][11] Enzymatic extraction has also been combined with ultrasound [10] and three-phase partitioning [12] to enhance oil recovery. Recently, reactive extraction has been demonstrated whereby extraction and transesterification processes were performed in a single step.…”
Section: Introductionmentioning
confidence: 99%